Anthropogenic nitrogen and phosphorus inputs in a new perspective: Environmental loads from the mega economic zone and city clusters. (10th February 2021) - Cui, Meng; Guo, Qingjun; Wei, Rongfei; Wei, Yujun
Abstract: The imbalance of regional development affects anthropogenic nitrogen and phosphorus (ANP) inputs pattern in a mega economic zone, and as an engine of regional development, a city cluster contributes to a more complicated spatiotemporal heterogeneity of ANP. This study estimates ANP loads of Yangtze River Economic Zone (YREZ) using statistics (2011–2017) that included industrial, agricultural, and living data for the first time. The impact of regional imbalanced development and city clusters on spatiotemporal heterogeneity of ANP inputs combined with socio-economic factors were analyzed, and the GM (1, 1) model was used to forecast the ANP changes by 2030. The results show YREZ has relatively high fluxes of anthropogenic N (11.8 tons km −2 yr −1 ) and P (1.8 tons km −2 yr −1 ) in comparison to other watersheds in the world. Hotspots are mainly concentrated in city clusters, which contribute to more than 60% of ANP within one-third of the economic zone' area. Since 2011, the anthropogenic N and P inputs of YREZ have decreased by 2% and 6%, respectively. The urbanization in eastern provinces has not led to an increase in ANP, but the underdeveloped areas are still at the stage of development with high burden. Although ANP is continuing to decline (2017–2030), the mid-western city clusters is still maintaining high ANP inputs and their decline is smaller than the average of YREZ (−5% N,  −14% P). Furthermore, the ANP inputs from the entire YREZ are deteriorating water ecology in an estuary, and their negative impact is greater than the delta region. Therefore, to achieve sustainable development of YREZ, the key is to accelerate the green development of urbanization in the mid-western regions. However, the improvement of estuarine water environment requires joint efforts throughout the entire economic zone. Highlights: Hotspots of N and P inputs of economic zone are concentrated in city clusters. N and P loads in city clusters accounts for more than 60% of economic zone. Economic zone effects the estuary water quality profoundly more than the local. Agricultural sources contribute most N and P inputs to the economic zone.